PENGARUH MOTIF MENONTON BERITA OLAHRAGA KABAR ARENA DI TV ONE TERHADAP KEPUASAN MENONTON MAHASISWA JURUSAN PENDIDIKAN OLAHRAGA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Alfi "; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The media has a huge influence on the direction of public life. One of the mass media that is around us is Media Television. Television is a medium of mass communication in the form of audio-visual which has several functions including informative, entertainment, and education. So many programs on television, so that people have a lot of choice of programs or information in accordance with the needs. In the theory of Uses and Gratification audience basically using the mass media based on certain motives, where the media is considered trying to meet the needs of the audience called as an effective medium. Students are part of the society who have needs of television media in an effort to meet the information needs. Among the programs the student needs is a sports news program, the needs met by the private television media through the TV One sports news program Kabar Arena. The purpose of this study is to determine how much influence the motive watching sports news on TV One Kabar Arena to watch the satisfaction of the Department of Physical Education Student Teaching and Education Faculty of the University of Riau. The method used in this research is quantitative method of explanation, the researchers collected data using questionnaires. The location of this research is on the campus of the University Department of Physical Education Guidance and Counseling is located at street Paus No. 5 Rumbai, Pekanbaru City - Riau. The number of samples for this study were 74 respondents. Sampling using random sampling techniques. To know how much influence these two variables, the researchers used a simple linear regression analysis. For data processing questionnaire, carried out using statistics program Product And Service Solution (SPSS) Windows version 17. These results indicate that the influence of motive watching sports news on TV One Kabar Arena on satisfaction Student Department of Physical Education Teaching and Education Faculty of the University of Riau, the regression coefficient values obtained in this study is Y = 9.603 + 0.806 X 0.001 significance level smaller of α = 0.05. This means that there is influence between watching sports news on TV One Kabar Arena to watch the satisfaction of the Department of Physical Education Students FKIP University of Riau 58.9% and in the category of influential medium. The percentage shows that the satisfaction of respondents watch sports news can be met. So that H0 is rejected and Ha is accepted. Keywords: Motif Watching, Sports News, Satisfaction Watching,Kabar Arena on TV One.